Humoral response and neutralization capacity of sheep serum inoculated with natural and Cobalt 60-irradiated Crotalus durissus terrificus venom (Laurenti, 1768) - Netto, D. P.; Chiacchio, S. B. [UNESP]; Bicudo, P. L. [UNESP]; Alfieri, A. A.; Nascimento, N. (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 2002)
The aim of this work was to investigate antigen irradiation on crotalic antivenom and the capacity of sheep as serum producers. Twelve sheep in two groups of six were inoculated with Crotalus durissus terrificus venom. One group was inoculated with natural venom (NV) and the other with Cobalt 60 gamma-irradiated venom (IrV). Three antigen doses were given to the animals at monthly intervals for immunization. The toxic activity of the venom was assessed by LD50 determination in mice. Blood samples were collected weekly analyses of serum neutralization capacity and potency. At the end of the experiment, the animals were challenged with a LD50 for sheep showed no signs of envenoming. These results showed that toxicity of the irradiated venom was 4.4 times less than the natural venom. The sera from the irradiated group neutralized LD50 14.6 times, and the sera from the natural group 4.4 times. Sera from the irradiated group were five times more potent. The two groups did not present clinical alterations. The results of this study show the potential for using sheep in crotalic antivenom production. The use of irradiated venom in sheep immunization induces a powerful and lasting humoral immune response shown by both the in vitro neutralization and potency tests and by the indirect ELISA antibody level detection technique.
Keywords: gamma irradiated crotalic antisera; snake venom; ELISA; sheep; Crotalus durissus terrificus; cobalt60